Optimalisasi Kualitas Pembelajaran Ekonomi Abad 21 melalui Pendampingan Guru SMA di Kabupaten Kediri Berbasis Deep Learning Pedagogis - M. Anas; Hariyono Hariyono; Mochamad Muchson; Forijati Forijati; Surya Ayu A.; Fatimatur R.; Rika Riwayatiningsih (Pusat Riset dan Inovasi Nasional, 2026)
21st-century economics learning demands strengthening reasoning, economic literacy, digital literacy, and contextual problem-solving skills. However, learning practices in high schools are still teacher-centered and oriented towards mastery of concepts, thus not fully supporting reasoning and reflective learning. This community service activity aims to improve the quality of 21st-century economics learning through mentoring high school teachers in Kediri Regency based on pedagogical deep learning. The mentoring is designed to strengthen reasoning-based learning design, pedagogical integration of technology, and the development of authentic assessments. The activity was implemented using a mixed-method approach with a pre-experimental one-group pretest-posttest design on 27 economics teachers who are members of the Kediri Regency Economics MGMP. Data were collected through pedagogical competency questionnaires, learning observations, and teaching tool documentation, then analyzed descriptively and inferentially. The results showed an increase in teachers' pedagogical competency after mentoring, reflected in increases in mean and median scores and a decrease in score variation. Paired sample analysis showed a strong and significant relationship between conditions before and after mentoring, confirming the consistency of changes in individual teachers. These findings confirm that pedagogical deep learning-based mentoring is effective in optimizing the quality of 21st-century economics learning and is relevant as a model for continuous teacher professional development to support the implementation of national education policies and the Independent Curriculum.